Agreeing on Efficient Emissions Reduction - Olivier Bos; Béatrice Roussillon; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2013)
We propose a simple mechanism providing incentives to reduce harmful emissions to their efficient level without infracting upon productive efficiency. The mechanism employs a contest creating incentives among participating nations to simultaneously exert efficient productive and efficient abatement efforts. Participation in the most stylised form of the scheme is voluntary and individually rational; all rules are mutually agreeable and are unanimously adopted if proposed. The scheme balances its budget and requires no principal. In a perhaps more realistic stochastic output version which could potentially inform policy decisions, we show that the transfers required by the efficient mechanism create a mutual insurance motive which may serve as effective rationale for the (gradual) formation of International Environmental Agreements.
Keywords: C70; D70; H40; Q50; 330; climate policy; contests; agreements; efficiency